Bagaimana Penerapan Aplikasi Quiz Interaktif dalam Meningkatkan Hasil Belajar Operasi Hitung Siswa ? - Idhi Agung Mulyawan; Suriswo Suriswo; Rahmad Agung N (Jurnal Karya Pendidikan Matematika, 2026)
The rapid development of digital technology in education provides teachers with opportunities to create more interactive and engaging learning experiences. In Grade 5 Mathematics, the topic of mixed arithmetic operations is often challenging for students, as it requires a strong understanding of the order of operations, accuracy, and intensive practice. This study aims to analyze the implementation of interactive quiz applications and their impact on improving students’ learning outcomes in mixed arithmetic operations. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects were 30 fifth-grade students from an elementary school. Data were collected through learning outcome tests, student activity observations, questionnaires, and documentation. The findings revealed a significant improvement in students’ learning outcomes, with the average score increasing from 63 in the pre-cycle to 74 in Cycle I and reaching 86 in Cycle II. Students also demonstrated highly positive responses toward the use of interactive quiz applications, noting that the learning process became more enjoyable, engaging, and easier to understand. Therefore, it can be concluded that interactive quiz applications are effective tools for enhancing students’ mastery of mixed arithmetic operations in elementary school mathematics.